Family farming in Alto Guaporé (MT), Brazil: non-agricultural incomes as an adaptation strategy to environmental changes (Polis (Santiago), 2018)
This paper analyses the adaptive capacity of a group of family farmers whose livelihoods are based on non-agricultural income from social transfers in the face of changes caused by global environmental changes. There is a long history of adapting to their impacts, managing the risks and dangers of their consequences. In order to demonstrate that vulnerability has a social dimension and is contingent on the conditions of the functioning of the institutional environment, aspects frequently neglected in the literature on the problem, a semi-structured questionnaire was applied consisting of questions that aimed to portray the social, economic, productive, environmental and institutional conditions to which they are subject in order to mobilize and make their social reproduction viable. The initiatives mobilized by these families to make their livelihoods viable demonstrate that the capacity to adapt is unequal, pointing out that social factors are determinants and fundamental to the capacity to adapt at all scales.
Keywords: Vulnerability; global environmental changes; production strategies; family farming